Effect of titanium and vanadium nano-carbide size on hydrogen embrittlement of ferritic steels - Tim Boot; Pascal Kömmelt; Hans J. C. Brouwer; Amarante Böttger; Vera Popovich (npj Materials Degradation)
Abstract The effect of TiC and VC nano-precipitate size on the hydrogen embrittlement of ferritic steels was studied in this work. Steels containing two size distributions (10 nm or less and 10 - 100 nm) of TiC and VC carbides are subjected to tensile tests in-situ in an electrochemical hydrogen charging environment. Hydrogen is found to be trapped in interstitial matrix sites on the precipitate/matrix interface with activation energies of 14 - 20 kJ/mol and inside misfit dislocation cores with energies of 27 - 37 kJ/mol. All steels are embrittled by 15 to 20%, except the TiC steel with semi-coherent carbides up to 100 nm, which is embrittled by 37%. This is caused by accelerated intergranular fracture as a result of hydrogen trapped in dislocation pile-ups around grain boundary precipitates. The steel with coherent VC nano-carbides retained the highest strength and ductility during in-situ testing. This is therefore the optimal carbide configuration for use in hydrogen environments.